(untitled) (Research, Society and Development, 2021)
Objective: to identify the main Nursing Diagnoses among users of a Psychosocial Care Center for Users of Alcohol and Other Drugs in Caucaia-CE. Methodology: exploratory-descriptive, documentary, quantitative study carried out at CAPS AD in Caucaia-CE. Among the 1020 active medical records, after the sample calculation, 200 medical records were chosen for analysis. Data were collected between December 2019 and April 2020, using a previously developed instrument, analyzed by simple descriptive statistics and based on NANDA-I (2018-2020) for the identification of the main Nursing Diagnoses; and discussed based on the relevant literature. Results: The users registered profile was mostly male, young adults, single, with incomplete elementary education, performing some type of occupation, being the alcohol as preferred substance. 37 Nursing diagnoses were identified, with predominance of those focused on the problem, followed by health promotion diagnoses. Regarding the analysis of risk diagnoses and focusing on the problem diagnoses, three subcategories emerged: 1) Problems of coping and self-perception; 2) Self-directed problems; and 3) Biological, physical, psychological and social problems. Substance abuse emerged as a related or risky element for most of these statements. Conclusion: Considering the complexity that involves nursing care in the context of Mental Health, it is pointed out that the survey of Nursing Diagnoses in this scenario is a primary tool to understand individuals in their singularities and outline interventions aligned to their nursing care needs.